Behavior of Pregnant Women In Pregnancy Examinations In Manisa Village, Baranti District - Thalib, Kiki Uniatri; Yulis, Dian Meiliani; Hariati, Andi; Ambarwati, Eny Retna; Yanti, Penti Dora; Rahmawati, Agustini Liviana Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The occurrence of maternal deaths is related to direct causal factors and indirect causes. The direct causes of maternal death in Indonesia are still dominated by factors. by bleeding, eclampsia, and infection, while the indirect factors causing maternal death are because there are still many cases, 3 too late and 4 too late, which are related to access, socio-cultural, educational and economic factors. This research uses a combination method with a sequential explanatory design. The first uses quantitative methods, and the second uses qualitative methods. A quantitative approach is used to identify and explain variables that influence behavior such as knowledge, attitudes, facilities and encouragement of officers. A qualitative approach is used to support and complement quantitative research results. The chi-square test shows that there is a significant relationship between knowledge, facilities and encouragement of health workers on the behavior of pregnant women in pregnancy checks. P value = 0.001. If the significance value is <0.05, it is recognized that there is a statistically significant correlation. Meanwhile, attitudes show no statistical correlation. The logistic regression test shows that there is an influence between knowledge and facilities on the behavior of pregnant women. There are two substantial findings, namely regarding knowledge about antenatal care and the availability of facilities which influence the behavior of pregnant women in antenatal care.